The Y chromosome and its use in forensic DNA analysis. Issue 3 (24th September 2021) - Syndercombe Court, Denise
Abstract : Originally relatively ignored in forensic investigations because its genetic analysis lacks inference of individual identification, the value of Y chromosome analysis has been proven in cases of sexual assault, particularly where the amount of material left by a male assailant is limited in comparison with female DNA. All routine analysis of autosomal DNA, however, targets a gene ( AMELY ) on the Y chromosome in order to identify the sex of the DNA source and this is discussed in the context of the genetic structure of this male-specific chromosome. Short-tandem repeat markers on the chromosome are tested in dedicated multiplexes that have developed over time and these are described alongside international guidance as to their use in a forensic setting. As a marker of lineage, the Y chromosome provides additional tools to assist in the inference of ancestry, both geographical and familial and the value of Y chromosome testing is illustrated through descriptions of cases of criminal and historical interest. A decision to analyse the Y chromosome has to be considered in the context, not only of the circumstances of the case, but also with regard to the ethical questions it might raise, and these are discussed in relation to the cases that have been described in more detail in the accompanying online supplementary material.